PMO-177 Maximal boosting of innate immunity during pegylated interferon-α therapy is reached at 48 weeks in e-antigen positive chronic hepatitis B. (28th May 2012) - Gill, U S; Papadaki, M; Peppa, D; Micco, L; Li, L; Ushiro-Lumb, I; Foster, G R; Maini, M K; Kennedy, P T F
Abstract : Introduction: Stopping-rules now exist for Pegylated Interferon-α (PEG-IFNα) treated Chronic Hepatitis B (CHB) patients. Despite the utility of such strategies, the immunological mechanisms that drive HBV DNA and HBsAg decline remain poorly understood. Recent data have identified changes in a subset of NK cells in HBeAg negative disease, which may determine treatment response. However, HBeAg positive disease responds more favourably to PEG-IFNα; here we report on a longitudinal analysis of changes in the immune profile in this cohort, to define the effects of PEG-IFNα on innate immunity. Methods: PBMCs from a cohort of 17 HBeAg positive patients followed longitudinally at 3 monthly intervals pre, during and post PEG-IFNα therapy were utilised. Phenotypic analysis of NK cells was performed by multicolour flow cytometry. Changes in the immune responses were correlated with simultaneous measurements of ALT, HBV DNA and quantitative HBsAg levels (Abbott ARCHITECT). Results: PEG-IFNα increased CD56 bright NK cells by fourfold (mean fold change; MFC 3.7, p=0.0001). This was parallelled by the activation and proliferation of this subset, as marked by HLA-DR and Ki67 expression respectively (MFC 1.5 and 2.3, p=0.009 and p=0.0001 respectively). This increase was more marked at 48 weeks treatment, correlating with a nadir of HBV DNA and HBsAg. The activating (NKG2C and NKp30) and inhibitory (NKG2A) receptors were also analysed in this population. A twofold increase in NKp30 expression (MFC 2.27, p=0.04) was seen which was maximal at 48 weeks, while no significant change was noted for NKG2A and NKG2C. There was a twofold up-regulation of TRAIL expression on CD56 bright NK cells, which temporally correlated with ALT levels, (MFC 1.8, p=0.0001), this effect was most dramatic at 24 weeks of therapy and sustained to 48 weeks. Conclusion: PEG-IFNα therapy in this cohort enhances and activates CD56 bright NK cells. Similarly, TRAIL and NKp30 expression is augmented and sustained throughout treatment and all these effects are maximal at 48 weeks. The restorative innate immune changes begin early and increase throughout therapy in all patients. Thus, 48 weeks therapy may provide the optimal immunological conditions to introduce an oral-antiviral to achieve disease control in PEG-IFNα non-responders. Competing interests: None declared.